Le travail manuel en tant que conférence-performance et sa relation à la phénoménologie et l’écologie queer - Alžbeta Kuchtová; Meltem Yildiz (Svět Literatury)
In the first part of this text, we define performance-conference as an art form. The concept of performance-conference was examined by Tanya Bruguera. This concept implies that craft can constitute a political attitude. In the introduction, we show that traditional manual labor (through the symbolism of bread, harvest and sourdough) is used and appropriated by right-wing populist dis course in Slovakia. In the second part of this text, we weave a link between Husserlian phenomenology and Sara Ahmed’s queer phenomenology to propose a phenomenological analysis of sourdough. The sourdough is interpreted here as a queer bacterial community that reproduces itself. Finally, we arrive at Myra J. Hird’s concept of hyper-sex, which describes the reproduction of bacteria. The conclusion shows that the reproduction of bacteria (of sourdough) deconstructs the right-wing discourse of traditional heteronormative reproduction. We choose to describe sourdough as queer in order to protest against the compulsory castration of trans people and other forms of oppression of the queer community in Slovakia and the Czech Republic. In this sense, manual labor (the performance, the cook) here constitutes a foundation for political action — in reference to the craftivism movement (Betsy Greer, Kundy Crew).